GEOPOLITICS AND THE PERMANENT SIGNIFICANCE OF SPACE IN INTERNATIONAL POLITICS - Radojević, Slobodan (National interest, 2024)
Geopolitics studies the geographical basis of power in international relations, therefore it occupies a central place in our research, because the work considers the role of space or territory in international relations, i.e. international politics. The paper starts from the concept and importance of the study of geopolitics and its place and role in international relations, and in this sense the permanent significance of space in international politics is highlighted. Namely, in one period there was a decline in the role of the state in international relations and thus a “crisis of the importance of space”. Space was neglected in social science theories, even in political theory. However, in geopolitical practice the situation was quite different. To some extent, the paper shows the understanding of space from the point of view of geoeconomics. Geopolitics has come a long way from being a disputed scientific discipline to the place it occupied in the system of sciences or scientific construction as a complex synthetic science. With globalization, there has been a shift in its center of gravity, which is certainly space, i.e. there was a neglect of its importance and the emphasis on the old and the birth of other scientific disciplines and sciences. Thus there was a shift and focus from classical geopolitical considerations to postmodernism. But it seems that these trends were premature and hasty and that there was no end of geopolitics, or rather no end. It is quite clear that space and territory are “in the game” again, or rather they were never “out of the game”. This fact is becoming more and more present every day, and therefore more and more clear considering the wars raging in the world and the spaces and territories that are occupied again and again. The area of Heartland is still today the axis of the entire Eurasian geopolitical dynamics. The world is preoccupied with wars in Eurasia and the Middle East. The constant conflict and confrontations do not stop either on the Korean peninsula, or between China and Taiwan. It seems that the entire area of Rimland represents one huge front, in some parts of which wars are raging with a large number of human casualties. Even the long-disputed geopolitical concept of land-sea has been resurrected like a phoenix bird. Actually, from the point of view of classical geopolitical conception, it is an example of thalassocratic expansion of the Rimland to the detriment of the Heartland, while on the other hand we had a tellurocratic restoration of the Heartland. Furthermore, the expansion of NATO itself was a real example of the struggle for space. Confrontations and conflicts do not stop in the North, Baltic, Mediterranean, Aegean Sea, Black Sea, Red Sea, South China Sea, but also in other peripheral seas of the Indian and Pacific Oceans. The current migrant crisis, wars, terrorism, climate change and other security challenges and threats to the modern world are just another confirmation of the “return” of classical geopolitical argumentation. All of this puts the classical geopolitical conception in the foreground when considering these conflicts and instability. Therefore, the paper, by applying a comparative analysis, aimed to show how disastrous is the neglect of the legality of classical geopolitics in scientific and professional circles. Considering examples of processes and events in international politics, the author concludes with a analysis that the approach of classical geopolitics is the most suitable for their scientific explanation. In the paper, the author argues that events in international relations have re-actualized the issues of geopolitics and highlighted the importance of space in international politics. Territory and space have not lost their importance for man, and it is shown again and again how geopolitical reasons are present in the struggles for possession or holding them.
Keywords: geopolitics; space; territory; geoeconomy; international politics